(untitled) (Economic and Political Thought, 2011)
The article is a part of broader research on the European Neighbourhood Policy and an attempt to answer a question about its significance and dimension in the Common Foreign and Security Policy and the Common Foreign and Defence Policy. The main theme of the article is an analysis of the thesis that the ENP is a sign of the existence of the Union’s global policy, and a comparison with a statement that it is nothing else than actions towards the countries neighboring the European Union undertaken on an ad hoc basis in order to enlarge the European security zone.